2019
DOI: 10.1002/ecs2.2616
|View full text |Cite
|
Sign up to set email alerts
|

Tree mortality submodels drive simulated long‐term forest dynamics: assessing 15 models from the stand to global scale

Abstract: Models are pivotal for assessing future forest dynamics under the impacts of changing climate and management practices, incorporating representations of tree growth, mortality, and regeneration. Quantitative studies on the importance of mortality submodels are scarce. We evaluated 15 dynamic vegetation models (DVMs) regarding their sensitivity to different formulations of tree mortality under different degrees of climate change. The set of models comprised eight DVMs at the stand scale, three at the landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 82 publications
4
101
0
Order By: Relevance
“…The dClim rule uses the change in local climate associated with a shift in elevation as a proxy for adaptiveness. This study demonstrated that varying the influence of the dClim rule can have a significant impact on future carbon and species composition estimates; similar results were reported in Diaz et al [37] and Bugmann et al [49]. Users of Climate-FVS must inspect results to ensure they are reasonable and consider the influence of parameterization, particularly with regard to the dClim rule.…”
Section: Carbon Trendssupporting
confidence: 85%
See 2 more Smart Citations
“…The dClim rule uses the change in local climate associated with a shift in elevation as a proxy for adaptiveness. This study demonstrated that varying the influence of the dClim rule can have a significant impact on future carbon and species composition estimates; similar results were reported in Diaz et al [37] and Bugmann et al [49]. Users of Climate-FVS must inspect results to ensure they are reasonable and consider the influence of parameterization, particularly with regard to the dClim rule.…”
Section: Carbon Trendssupporting
confidence: 85%
“…It is not known to what degree, if any, and how fast this mortality will occur in real forests though existing research indicates that climate-induced mortality from drought, wildfire, and insect epidemics could be widespread [50,51]. Climateinduced mortality functions vary among climate sensitive vegetation models, and a recent study found Climate-FVS was noted to be more sensitive to climate-induced mortality than non-climate induced mortality (e.g., mortality due to increasing stand density) among the models tested [49]. Toward the end of the simulations, after the dClim rule affected tree mortality rates, carbon projections stabilized or began to increase.…”
Section: Carbon Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the development of DVMs is challenging since many processes are involved and interact across temporal and spatial scales (Bugmann 2001, Keane et al 2001, Price et al 2001). Thus, large uncertainties remain regarding the quantification of the ecological processes that govern forest dynamics, including both structural and parameter‐related uncertainties (Fortin et al 2009, Hlásny et al 2014, Horemans et al 2016, Reyer et al 2016, Neumann et al 2017, Huber et al 2018, Bugmann et al 2019). Not surprisingly, a plethora of model formulations are used in DVMs, but they are rarely benchmarked rigorously.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, a plethora of model formulations are used in DVMs, but they are rarely benchmarked rigorously. Yet, alternative process formulations have the potential to strongly alter simulation results, particularly when DVMs are applied for climate change impact assessments (Nishina et al 2015, Horemans et al 2016, Bugmann et al 2019).…”
Section: Introductionmentioning
confidence: 99%